Penetapan Kadar Amilosa Pada Beberapa Beras Hitam (Oryza Sativa L.) Lokal Jawa Barat - Tita Kartika Dewi (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
Rice in the world consists of several types, including white rice, brown rice, black rice, and brown rice. Rice is also grouped into two groups, namely glutinous rice containing high amylopectin (low amylose) and non-glutinous rice, namely rice with low amylopectin content (high amylose). Amylose content determines the quality of taste, fluffiness and other physical properties. Rice that has a high amylose content has the properties of soft/hard rice, while rice that has a low amylose content has the character of a fluffier rice. This research was conducted with the aim to determine the amylose content found in black rice, especially local West Java. The research was conducted in October 2018 at the BB-PADI Sukamandi Subang laboratory. The tools used are beakers, measuring flasks, funnels, analytical scales, spray bottles, measuring pipettes, and a spectrophotometer. The materials used were Bandung black rice, Subang black rice, Bogor black rice, and Indramayu black rice, amylose standard solution, methylene blue indicator, 0.02 N HCl, distilled water, 95% ethanol solution, NaOH solution, iodine solution, and others. Determination of amylose content using the spectrophotometric method (AOAC, 1999), was carried out in two stages, namely: the Standard Curve Preparation Stage and the Sample Determination Stage. From the research results, the following data were obtained: the amylose content of black rice from Subang was 12.72%w/b, the amylose content of black rice from Bandung was 17.21%w/b, the amylose content of black rice from Bogor was 13.67%w /w and the amylose content of black rice from Indramayu was 21.18% w/w. Based on the results of the study, it can be concluded that black rice from three regions in West Java, namely Bandung, Subang and Bogor, is included in the low amylose content category (10-20%) and black rice from Indramayu is included in the medium amylose content group (20-25%). The lowest amylose content was owned by black rice from Subang with a value of 12.72% and the highest amylose content was owned by black rice from Indramayu with a value of 21.18% w/w.